Development of breast cancer detection system using digital image - Norlailah, Lanisa (2012)
Breast cancer is one of the most common cancer affecting women around the world. Mammography is the most known and effective method to detect early sign of breast cancer. However, due to some weaknesses in mammography such as painful procedures and radiation, researches introduce another diagnosis method which is by analysing thermal image. The purpose of this project is to design a system to detect the signs shown in mammogram and thermal image using Image Processing Technique applied to MATLAB. Image processing techniques can be divided into several elements. The elements are image acquisition, image preprocessing,image processing, feature extraction, object classification and classification decision. Both type of images then analyse step by step according to the elements. Mammogram images are analyse using morphology technique before features extraction which then lead to the classification of the image into 3 classes („Normal Fatty breast‟, „Abnormal Fatty breast‟ and „Glandular breast). For thermal image, the distribution of heat around the breast will be the features extracted and analysed. The different range of heat in the image will be used to specify the possible area of cancer. This project also includes the construction of Graphical User Interface (GUI) so that the system is more users friendly.